Prevalence of high-risk behaviors in reproductive age women in Alborz province in 2019 using unmatched count technique - Samira Bahadivand; Amin Doosti-Irani; Manoochehr Karami; Mostafa Qorbani; Younes Mohammadi (BMC, 2020)
Abstract Background Our knowledge on the prevalence of high-risk behaviors among women of Alborz is not reliable due to the sensitivity of the issue. This study aimed to estimate the prevalence of seven risk behaviors among the reproductive age women in Alborz Province, Iran. Method In this cross-sectional study, 2000 women were randomly selected from a registered healthcare system in 2019. A researcher-made questionnaire was used to collect the required data. The prevalence of the risk behaviors including drug abuse, hookah, alcohol drinking, tobacco smoking, extramarital intercourse, and gambling was estimated using the unmatched count technique, and the prevalence rate was reported at a 95% confidence interval. Results The response rate for this study was 95%. The estimated prevalence for drug abuse, hookah, alcohol drinking, tobacco smoking, extramarital intercourse, and gambling were 3% (95%CI: 2.78 to 3.22), 10.5% (95%CI: 10.29 to 10.71), 7% (95%CI: 6.78 to 7.22), 10% (95%CI: 9.78 to 10.22), 8.7% (95%CI, 8.29 to 8.71), and 7.5% (95%CI, 4.71 to 7.28), respectively. Conclusion High risk behaviors are highly prevalent among Iranian women. Enforcing laws, prohibition, marketing restrictions, increasing taxation, expanding treatment, promoting condom distribution and providing community-based service are recommended to reduce the effects of high risk behaviors among women.